Behaviour of Abutilon theophrasti in Different Climatic Niches: A New Zealand Case Study - Ghanizadeh, Hossein; James, Trevor K. (Frontiers in Plant Science, 2022)
Abutilon theophrasti Medik. was initially introduced into New Zealand in the 1940s. Despite its introduction approximately 70 years ago, A. theophrasti infestation in New Zealand has been naturalized to one region only, although climate-based simulation models predicted that A. theophrasti establishment could almost occur in all New Zealand agricultural lands. One possible reason for this discrepancy is that the likelihood of establishment of A. theophrasti may vary across various localities as the climate in New Zealand is complex and varies from warm subtropical in the far north to cool temperate climates in the far south. The objective of this research was to assess and compare the likelihood of A. theophrasti establishment across various localities in New Zealand. For this, experiments were laid out across different regions in New Zealand to assess vegetative and reproductive characteristics in naturalized and casual populations of A. theophrasti. The results showed that the growth and development of both populations varied across different regions, possibly due to variable climatic and geographical conditions such as local temperatures and daily solar radiation. It appears that A. theophrasti is, however, able to grow in many regions in New Zealand, but this species is unlikely to establish and become problematic in the lower half of South Island, where the temperature is lower than optimal temperatures required by this species. A casual population was found to grow better at the early stage of growth compared to a naturalized one. However, both populations reproduced similar amounts of seed in all regions. Overall, the variable vegetative and reproductive responses recorded for A. theophrasti in different locations may suggest that the invasion dynamic of this weed species is unlikely to be similar across different climatic niches in New Zealand.